Air transportation and tourism interactions and actions for competitive destinations: the case of Cyprus - Liasidou, Sotiroula; Garanti, Zanete; Pipyros, Kosmas (My University, 2022)
Purpose – Air connectivity is one of the most important aspects of tourism development, especially for island state destinations (ISD) which rely on air travel for accessibility. The complexity of the tourism industry necessitates close interaction among involved stakeholders to ensure successful policy implementation of air transportation operations that facilitate tourism mobility at a destination. Design/methodology/approach – In this paper self-administered questionnaires in a structured format were distributed to 200 managers. Additionally, seven unstructured follow-up interviews were conducted to enrich the content and better support the conclusions. Findings – The results of the study suggest that air transportation and connectivity are not fully integrated with tourism policy and strategy planning. Yet it is crucial that a stakeholder approach is adopted that accounts for the needs of diverse stakeholders and airline strategies, along with a diversified tourism policy that can establish Cyprus as year-round destination. Originality/value – The role of the airline industry in overall tourism strategy and policy is examined and the unique problems and challenges ISDs like Cyprus face in developing as a tourism destination and overcoming tourism seasonality are underlined.
Keywords: Airline industry; Island states; Seasonality; Cyprus; Tourism policy; Self-administered questionnaires